Peroral endoscopic myotomy for achalasia—a review - Kohn, Geoffrey Paul (Annals of Laparoscopic and Endoscopic Surgery; Vol 4 (September 2019): Annals of Laparoscopic and Endoscopic Surgery, 2019)
Definitive treatment of achalasia usually involves disruption of the muscle fibers of the lower esophageal sphincter (LES). Over the past few decades the most common procedure to achieve this has been laparoscopic Heller myotomy (LHM) with partial fundoplication. Recently, peroral endoscopic myotomy (POEM) has been increasingly utilized. This manuscript reviews the current state of the POEM procedure in the treatment of achalasia. Safety and efficacy of the procedure have been demonstrated. Unanswered questions remain regarding the long-term incidence and implication of gastroesophageal reflux, as well as any possible benefits of the omission of an antireflux fundoplication when compared to Heller myotomy (HM).